ICT impact on labor productivity and employment in Russia - Sergy Perminov; Elena Egorova (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
This paper is concentrated on estimating the ICT impact on output growth and labor productivity in Russia in 1990-2001. Three major industry groups are being distinguished: ICT-producing industries, ICT-using industries and non-ICT industries. This industry classification, used by Bart van Ark1 etc., will help us analyze structural changes in Russian economy and make cross-country comparisons. National accounts and other data published by the Russian State Statistics Committee were used to obtain the data on total output and value added, deflators for all products and services. The results show that the growth rates in ICT-producing and ICT-using industries were much higher than in non-ICT industries, although an essential delay of ICT spreading still takes place in Russia in comparison with developed countries. · The ICT-producing sector in Russia is essentially smaller as compared to the USA and Europe. Dramatic decrease in this sector in Russia in 1990-1995 was changed by labor productivity growth in 1996-2000, but it is slower than in the developed countries. · The tendency of labor productivity growth in the ICT-using sector changes from essential fall to relatively rapid increase. · The decrease of labor productivity in the non-ICT sector during the crises of 1990-1995 changed to slow growth in 1996-2000, which can be considered stagnation. · Productivity growth and employment decrease in manufacturing is a common feature of all of the mentioned sectors in 1995-2000. · The financial collapse of 1998 had a generally positive influence on labor productivity · The tendencies of growth in the ICT sectors in Russia after 1998 remain in 2001-2003 (with some exceptions). However, these generally positive tendencies of ICT influence on economic growth in Russia do not provide much optimism because the 'surface' reserves will soon be confined or reduced especially in trade, finance, and insurance where ICT diffusion does not require large investment and gives a rapid return. It is becoming possible to give new quality to economic growth on the base of the ICT because 'innovations' and 'human capital' may become its major driving force. It will help compensate the expected sharp decrease of population capable for working in the next 10 years.
Keywords: 330; Informationstechnik; Arbeitsproduktivität; Erwerbstätigkeit; Russland